Changes in cytokines, leptin, and IGF-1 levels in overtrained athletes during a prolonged recovery phase: A case-control study - Joro, R.; Uusitalo, A.; DeRuisseau, K. C.; Atalay, M. (Journal of Sports Sciences, 2017)
We investigated how cytokines are implicated with overtraining syndrome (OTS) in athletes during a prolonged period of recovery. Plasma IL-6, IL-10, TNF-a, IL-1ß, adipokine leptin, and insulin like growth factor-1 (IGF-1) concentrations were measured in overtrained (OA: 5 men, 2 women) and healthy control athletes (CA: 5 men, 5 women) before and after exercise to volitional exhaustion. Measurements were conducted at baseline and after 6 and 12 months. Inflammatory cytokines did not differ between groups at rest. However, resting leptin concentration was lower in OA than CA at every measurement (P < 0.050) but was not affected by acute exercise. Although IL-6 and TNF-a concentrations increased with exercise in both groups (P < 0.050), pro-inflammatory IL-1ß concentration increased only in OA (P < 0.050) and anti-inflammatory IL-10 was greater in CA (P < 0.001). In OA, exercise-related IL-6 and TNF-a induction was enhanced during the follow-up (P < 0.050). IGF-1 decreased with exercise in OA (P < 0.050); however, no differences in resting IGF-1 were observed. In conclusion, low leptin level at rest and a pro-inflammatory cytokine response to acute exercise may reflect a chronic maladaptation state in overtrained athletes. In contrast, the accentuation of IL-6 and TNF-a responses to acute exercise seemed to associate with the progression of recovery from overtraining.